PHARMACOLOGICAL NEUROPROTECTIVE EFFICACY OF ESSENTIAL OILS (EO) BASED AROMATHERAPY: AN INSIGHT - Pant, Arushi; Agarwal, Shriya; Jha, Kanupriya; Singh, Manisha (Journal of Biomedical and Pharmaceutical Research, 2019)
Aromatherapy or Essential oil therapy is attributed towards the field of conventional, alternative or complementary therapies which requires essential oils and other aromatic plant compounds. Essential oils (EOs) belong to the class of highly volatile compounds which, due to their higher concentrated natural constituents acquire unique properties and hence, are being used for its wide range of therapeutic health benefits. Their benefits widely range from being a potential antimicrobial, antidepressant, antiviral and antiseptic agents to the elevator of many CNS related behaviours like - anxiety, stress, wisdom, memory, attention, relaxation, sedation, and sleep. Furthermore, the effects on mood, pain, and perception too are being influenced by the use of essential oils. It also helps in the treatment of epilepsy, stress, dementia by giving calming and soothing effects to the nerve cells and is also effective against dementia and on the treatment of Alzheimer’s disease.